2013
DOI: 10.1002/jcc.23296
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and structural changes of small water clusters on ionization

Abstract: Despite utmost importance in understanding water ionization process, reliable theoretical results of structural changes and molecular dynamics (MD) of water clusters on ionization have hardly been reported yet. Here, we investigate the water cations [(H2O)(n = 2-6)(+)] with density functional theory (DFT), Möller-Plesset second-order perturbation theory (MP2), and coupled cluster theory with single, double, and perturbative triple excitations [CCSD(T)]. The complete basis set limits of interaction energies at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 78 publications
2
49
0
1
Order By: Relevance
“…The relative energies of these isomers are also included for quantitative comparison. The obtained AIP for W 1 without ZPVE correction is 9.89 eV, which coincides with the reported value [46].…”
Section: Relationship Between the Structure And Energysupporting
confidence: 88%
See 1 more Smart Citation
“…The relative energies of these isomers are also included for quantitative comparison. The obtained AIP for W 1 without ZPVE correction is 9.89 eV, which coincides with the reported value [46].…”
Section: Relationship Between the Structure And Energysupporting
confidence: 88%
“…The detailed schemes of the hemi-bonded type are difficult to give a good account, so the relevant descriptions are omitted. Lee and Kim[46] deduced and ) and 4nR4 (neutral water molecule type). The four isomers reported by Do and Besley[47] are also found by us.Fig.…”
mentioning
confidence: 98%
“…Water molecules exist in the form of water clusters in bulk water due to strong HB interactions. It was reported that the interaction energy of H 3 O + –OH − is 46.9 kJ mol −1 , and it increases approximately 2.5-times when H 3 O + associates with an additional four water molecules24. Based on the two features, the combination of using sAuNT water with weak HBs in OER is proposed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Magnética Nuclear (RMN) onde gases dissolvidos na água parecem afetar a rede de ligações de hidrogênio e modificar a estrutura das nanobolhas ou das nanocavidades dos clatratos 34 . Além disso, a dinâmica de pequenos clusters de água é também marcadamente afetada pelo processo de ionização 20,35 . Neste contexto, tem sido sugerida a participação da sílica na formação de aglomerados de água; esta seria liberada a partir dos recipientes de vidro, utilizados normalmente na preparação dos medicamentos homeopáticos 36 .…”
Section: Evidências Importantes Têm Sido Fornecidas Por Experimentos unclassified